1975
DOI: 10.1172/jci108037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a molecular change in collagen on lung structure and mechanical function.

Abstract: A B S T R A C T Semicarbazide, a lathyrogen. was given to growing rats to elucidate the consequences of altering the molecular structure of fibrous proteins within the lung. Static pressure-volume (P-V) measurements during deflation of saline-filled lungs showed normal recoil pressure and compliance values within the physiological range of lung volume. Quasi-static P-V measurements were also normal during slow reinflation, even beyond physiological limits to a recoil pressure of 20 cm H20. However, the lungs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 27 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Increases in the maximal lung volume have been seen following elastase and collagenase treatment in hamsters. 33*34 However, it is not clear whether the increased extensibility is a function of elastic or collagen fiber derangement or the relationship between the Stanley et al 36 gave weanling rats (40-60 g) semicarbazide, a compound that blocks cross-linkages during collagen formation. Four to 6 weeks later they found that lung histology and morphology were normal, except when overinflated, when there was dilatation of terminal air spaces with rupture of alveolar septa and a greater Lm.…”
Section: Lung Volumes Pressure-volume Curves and Lung Morphometricsmentioning
confidence: 99%
“…Increases in the maximal lung volume have been seen following elastase and collagenase treatment in hamsters. 33*34 However, it is not clear whether the increased extensibility is a function of elastic or collagen fiber derangement or the relationship between the Stanley et al 36 gave weanling rats (40-60 g) semicarbazide, a compound that blocks cross-linkages during collagen formation. Four to 6 weeks later they found that lung histology and morphology were normal, except when overinflated, when there was dilatation of terminal air spaces with rupture of alveolar septa and a greater Lm.…”
Section: Lung Volumes Pressure-volume Curves and Lung Morphometricsmentioning
confidence: 99%
“…Adapted from human studies to measure ICP by colonometry [1][2][3], we for the first time present the feasibility of colonometry in mice to measure ICP as an outcome of colonic stretch-reflex contraction to assess colonic mechanical sensitivity. Infusion of a constant rate of saline into a hallow organ while measuring intra-organ pressures to assess the organ function has been used in pulmonary [38] and urodynamic [39,40] studies, and here in study of colonic function.…”
Section: Discussionmentioning
confidence: 99%
“…More than 10% of the lung's dry weight consists of collagen (Pierce and Hocott, 1960) and its function, as in other organs (Harkness, 1961), is to maintain structural integrity by virtue of its great tensile strength (Pierce and Ebert, 1965). If normal collagen synthesis is inhibited in experimental animals, the lungs are very friable and the alveolar walls and pleura may be ruptured by only moderate mechanical stress (Stanley et al, 1975). It is therefore proposed that pneumothorax and emphysema in the Marfan syndrome are further manifestations of the generalized connective tissue abiotrophy, perhaps due to a molecular defect in collagen, and that involvement of lung tissue renders it less able to withstand the wear and tear of everyday life.…”
Section: Discussionmentioning
confidence: 99%